Decoding Marine Genetic Resource Governance Under the BBNJ Agreement - Humphries, Fran (Sustainable Development Goals Series, 2025)
This open access book provides practical guidance for understanding the new treaty adopted in June 2023 that will change the way biodiversity is governed in about two thirds of the oceans known as areas beyond national jurisdiction (ABNJ). The Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction is an achievement for global cooperation in conservation, sustainability and equity. The treaty provisions in Part II on Marine Genetic Resource (MGR) governance were the most contentious element of negotiations, resulting in significant innovation and compromise. It has an ambitious framework with many details yet to be fleshed out after the treaty comes into force. There is no comprehensive guidance for stakeholders about what the treaty means for their current and future research and development (R&D) and commercialisation of MGR of ABNJ, digital sequence information and associated traditional knowledge. Through a detailed commentary and real world examples, this book interprets and analyses the treaty text to offer practical considerations, guidelines and tools to assist policy makers as well as scientists and commercial end users to align their R&D practices with the expected implementation of the treaty.